Scoring Card for Characteristics of Mother, Child, and Environtment in Early Stunting Detection Efforts - Nugraheni, Diah Eka; Yorita, Epti; Pravita, Ayu; Asih, Yusari (Jurnal Kesehatan, 2023)
Stunted children at an early age have lower fluid intelligence. 48.6% of children aged 7-8 years have less cognitive ability. This study uses a case-control research design. The sample in this study included 113 case groups and 113 control groups. The independent variables in this study were maternal anemia, Choric Energy Deficiency (CED) in pregnant women, pregnancy complications, maternal infection history, smoking habits, mother's height, age at pregnancy, mother's education, birth weight, birth length, gender of the baby, history of diarrheal infection, ARI, gestational age during pregnancy, birth gap, exclusive breastfeeding, weaning food, helminthiasis, child immunization, clean water, and family income. The dependent variable in this study is the incidence of stunting in children under five. The results showed that the variables related to stunting were maternal anemia, CED in pregnant women, mother's height, age at pregnancy, mother's education, birth weight, birth length, baby's gender, history of diarrheal infection, ARI, helminthiasis, and income. The analysis using the ROC obtained a confidence value of 8.5, which means very good, and the cut-off point that can be used in determining the risk of stunting is 8.5. It is necessary to socialize the use of stunting scoring cards to carry out early detection of toddlers to find out whether there is a risk of stunting so health workers can carry out proper assistance to apply the prevention efforts.